Impact of Value on Customer Retention of Fast Food Restaurants in Saudi Arabia - Al-Nsour, Iyad; Al-Sahli , Saud (The Arab Journal of Administration, 2024)
The study aimed to measure the impact of the value on customer retention in fast food restaurants in Riyadh. The customer value consisted of two types: financial value and non-financial value. In addition, the study aimed to identify statistical differences in customer retention in fast-food restaurants according to demographics. The research population is all Saudi customers of local and foreign fast-food restaurants in Riyadh. The actual population reached 7.9 million people in 2021. Non-probability sampling techniques and the convenience sampling method were used. The recommended sample size was 348 people. The electronic questionnaire on Google Drive and face-to-face distribution at fast food restaurants. The structural equation modeling SEM used. The results of the path analysis showed a positive statistical impact of customer value on customer retention in fast-food restaurants in Riyadh. Financial value is most influential on customer retention. The study also found no statistically significant differences in customer retention according to gender, age, and preferred brand while differences according to education and duration of dealings with the brand proved. Finally, the study recommended that workers in fast food restaurants should be trained in interaction and communication skills, the integration of marketing communication activities with customer value, and activating customer knowledge and relationship management in fast food restaurants in the Kingdom.